PECULIARITIES OF FUNCTIONAL WORKING STATE IN OPERATORS OF AIR TRAFFIC CONTROL SERVICE - Apykhtin, K. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
This article is devoted to functional working state exploration by HRV – measuring in operators of air traffic control service. It was established a prevalence of partial sympathetic baroreflexive activity in air traffic controllers. Engineering personnel was characterised by prevalence of partial activity of subcortical sympathetic ergotropic centres. There was shown more expressed shift to sympathotony and higher level of neuro-emotional tension in air traffic controllers, than in engineering personnel.